Phytochemical Analysis and Bioactivity Evaluation of Root Extract of Selinum tenuifolium Wall. from Nepal - Shrestha, Rajib Kumar; Maharjan, Prabal Singh; Shrestha, Bhupal Govinda (Journal of Nepal Chemical Society, 2025)
Since ancient time, the herbal medicinal plants have been widely used in the treatment of various ailments due to fewer or no side effects, cheap, and easy availability. This study aimed to evaluate the phytochemical screening, antioxidant, antibacterial, and anticancer activity of Selinum tenuifolium root methanol extract (STRM). Based on our information, this is the first study evaluating its anticancer activity. The antioxidant, antibacterial, and anticancer activities were determined by DPPH, agar plate well diffusion method, and MTT assay, respectively.  The preliminary phytochemical screening of STRM revealed the presence of various phytochemicals like alkaloids, glycosides, terpenoids, quinone, and carbohydrate. STRM showed dose-dependent moderate antioxidant activity (102.18 μg/mL IC50 value) (P < 0.05). STRM showed dose-dependent active antibacterial activity against S. aureus and no antibacterial activity against S. flexneri, E. coli, P. aeruginosa, and K. pneumoniae at 50 mg/mL concentration. The plant extract (STRM) showed dose-dependent active antibacterial activity against S. aureus with 9 mm ZOI at 25 mg/mL to 18 mm ZOI at 200 mg/mL concentration. The anticancer activity of STRM was dose-dependent moderate against HeLa (188.01 µg/mL IC50 value) cancer cells (P < 0.05).  Overall, STRM showed dose-dependent moderate antioxidant, active antibacterial, and moderate anticancer activity due to the synergistic effect of different phytochemicals present in the plant extract (STRM).